Kant’s Categorical Imperative and Mandatory Minimum Sentencing - Turner, Craig (2016)
Deterrence-based punishment systems are scattered throughout history, and exist in the American legal system today. One such method of deterrence prescribes mandatory punishments for violations of certain crimes, without regarding to underlying circumstances or an assessment of the the individual accused of such crimes. These types of sentencing requirements restrict judicial discretion and are designed to serve as an example for other would-be offenders. While perhaps justifiable under a utilitarian code of ethics, mandatory minimums are morally suspect when assessed through the lens Immanuel Kant’s Categorical Imperative. The fundamental premise of the second formulation of Kant’s Categorical Imperative rests upon human freedom and autonomy. By forcing individuals to personally serve punishments meant to deter others from committing the same crime can have the effect of treating such individual merely as a means to some other end. Because of this, mandatory punishments which seek to deter, and not rehabilitate offenders likely violate Kant’s Categorical Imperative. This Note examines the historical and current status of mandatory sentencing laws, and applies Kantian ethics to assess these laws’ morality